2012
DOI: 10.1074/jbc.m112.359562
|View full text |Cite
|
Sign up to set email alerts
|

Period of Irreversible Therapeutic Intervention during Sepsis Correlates with Phase of Innate Immune Dysfunction

Abstract: Background: Sepsis is a major health problem that can be investigated in experimental animal models. Results: Its etiology is divided into an early therapeutically reversible phase displaying a robust inflammatory response followed by a late therapeutically irreversible stage with reduced innate immune response. Conclusion: Mortality is associated with a late immune dysfunction. Significance: This study provides information for the potential window for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 71 publications
6
36
0
Order By: Relevance
“…Indeed, Flo et al previously showed that E. coli infection induced a robust expression of Lcn2 in hepatocytes, 14 and Wu et al reported that both bronchial epithelial cells and type II pneumocytes produced significant amounts of Lcn2 following pulmonary infection. 16 Conversely, we found that the kinetic expression of CRAMP in liver and lung followed an expression pattern similar to that observed for most of the inflammatory cytokines and neutrophil infiltration, 21 indicating that neutrophils may represent the main source of CRAMP in hepatic and pulmonary tissues following CLP-induced sepsis. Although CRAMP has also been detected in several other cell types such as monocytes and respiratory epithelial cells, 36 we cannot discard the possibility that other cells may contribute to some extent to CRAMP expression in these two tissues.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Indeed, Flo et al previously showed that E. coli infection induced a robust expression of Lcn2 in hepatocytes, 14 and Wu et al reported that both bronchial epithelial cells and type II pneumocytes produced significant amounts of Lcn2 following pulmonary infection. 16 Conversely, we found that the kinetic expression of CRAMP in liver and lung followed an expression pattern similar to that observed for most of the inflammatory cytokines and neutrophil infiltration, 21 indicating that neutrophils may represent the main source of CRAMP in hepatic and pulmonary tissues following CLP-induced sepsis. Although CRAMP has also been detected in several other cell types such as monocytes and respiratory epithelial cells, 36 we cannot discard the possibility that other cells may contribute to some extent to CRAMP expression in these two tissues.…”
Section: Discussionsupporting
confidence: 68%
“…35 We have previously observed that the initial recruitment of neutrophils within the first 6 h of CLP was followed by a rapid decline in the number of these granulocytes in both liver and lung. 21 We showed in this report that Lcn2 expression rapidly increased and reached a plateau expression a few hours after CLP (6 and 3 h for liver and lung, respectively). These results indicate that the kinetic of Lcn2 expression is not likely explained by the presence of neutrophils in these two tissues, but rather by other types of stimulated cells.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Animals also exhibit hypothermia during experimental abdominal sepsis (60)(61)(62), and therefore hypothermia has been proposed as an effective indicator of mortality (63). Indeed, our model of polymicrobial IAI shows strong association between hypothermia and mortality at 24 h postinfection.…”
Section: Figmentioning
confidence: 79%